Examining the Effects of Training According to Learning Styles on Self-care among Patients with Type 2 Diabetes - Amir Reza Saleh Moghadam; Farzane Hozhabr Araghi; Ali Bazzi; Hamidreza Behnam Voshani; Hossein Karimi Moonaghi (Mashhad University of Medical Sciences, 2017)
Background: Despite the implementation of new training programs, neglecting individual differences in terms of learning styles can be taken into account as one of the reasons for poor levels of self-care behaviors in patients suffering from diabetes. Aim: The purpose of the present study was to examine the effect of training according to the learning styles on self-care behaviors among individuals suffering from type 2 diabetes. Method: This randomized, controlled clinical trial was performed on 69 diabetic patients referring to Parsian Clinic in Mashhad, Iran, who were divided into experimental (comprised of four aural, visual, read-write, and kinesthetic-sensory groups based on the results of the VARK [Visual, Auditory, Read/Write, Kinesthetic] Learning Styles Questionnaire) and control (lecture-based education). Self-care training was also conducted during two sessions each two weeks on four domains of diet, exercise program adherence, blood glucose monitoring, and insulin intake. To analyze the data, independent samples t-test and Mann-Whitney U test were run, using SPSS version 21. Results: Based on the independent samples t-test, in the experimental and control groups, the total mean scores of self-care behaviors were not significantly different prior to the intervention (135.2±17.6, 129.7±27.6, respectively). However, a statistically significant difference was noted between the experimental and control groups regarding the total mean scores of self-care behaviors (164.1±7.6, 140.5±10.0, respectively; P=0.001). Conclusion: It was concluded that self-care training based on learning styles could be improved among patients with diabetes. The VARK Learning Styles Questionnaire could be used to facilitate this type of training through providing information about learning and teaching methods as well as using the media appropriate to individuals' learning styles.